Delayed diagnosis of traumatic hip dislocation mimicking Perthes disease in a child. (20th April 2011) - Singhal, Rohit; Perry, Daniel; Cohen, Daniel; Bruce, Colin
Abstract : Traumatic hip dislocations in children are uncommon, yet even trivial injuries may result in dislocation. Avascular necrosis (AVN) occurs in 3–6% of dislocations if reduction is performed within the first 4 h, however, the incidence rises to 66% if the reduction is performed 24 h after dislocation. Awareness and early identification is therefore critical to long term prognosis. The authors report a case of a relatively trivial trauma resulting in hip dislocation in a 5-year-old boy. This case is useful in highlighting that (a) hip dislocation may occur in children with relatively trivial mechanisms, (b) knee pain often indicates an underlying hip pathology and (c) traumatic AVN follows a similar course to Perthes disease and therefore may be management should be tailored in a similar manner to achieve containment within the acetabulum.